Analisis Faktor Penyebab Ketidakakuratan Kode Diagnosis Cedera di Rumah Sakit 'Aisyiyah Siti Fatimah Tulangan - Yuliani, Resta Dwi; Ariani, Suci; Widanti, Herista Novia (Politeknik Negeri Jember, 2025)
The accuracy of diagnostic and medical procedure coding depends on the completeness and clarity of information in medical records. A preliminary survey of 59 inpatient records showed that 23 were coded accurately, while 36 were inaccurate. This study aims to analyse factors contributing to inaccurate injury diagnosis coding at RS ‘Aisyiyah Siti Fatimah Tulangan. A descriptive design was used, with data collected through observation and interviews. Observations were conducted on 100 inpatient medical records of injury cases, and interviews involved two coders. The results showed that the fourth-character coding was accurate in 96 records (96%) and inaccurate in 4 records (4%), mainly due to non-specific diagnoses documented by physicians. For the fifth character, 53 records (53%) were coded accurately and 47 records (47%) inaccurately, primarily because the documentation did not specify whether the injury was open or closed. No records (0%) included accurate external cause codes, while all records (100%) were inaccurate, largely due to limited coder knowledge and the fact that coders were not trained medical record professionals. Hospitals are advised to improve clinical documentation, provide regular disease coding training, and strengthen collaboration between coders and physicians to enhance coding accuracy.